Multiple rectal neuroendocrine tumors: An analysis of 15 cases and literature review - Pang, Shu; Zong, Ye; Zhang, Kun; Zhao, Haiying; Wang, Yongjun; Wang, Junxiong; Liu, Chuntao; Wu, Yongdong; Li, Peng (Frontiers in Oncology, 2022)
Objective: Multiple neuroendocrine tumors (M-NETs) are rare in the rectum and there is no consensus on their characteristics and treatments. Here, we report 15 cases of rectal M-NETs and review the previous literature. We discuss the clinical characteristics, endoscopic features and pathological features of rectal M-NETs, aiming to analyze the treatments and follow-up strategies in combination with these characteristics. Materials and Methods: We retrospectively reviewed and analyzed the data of 15 patients with rectal M-NETs who were diagnosed and treated at Beijing Friendship Hospital, Capital Medical University. Their clinical data, endoscopic findings, pathological features and treatments were analyzed. Follow-up evaluations and literature review were performed. Results: In all, 14 male (93.3%) and 1 female (6.7%) were recruited. The average age at diagnosis was 55.7 years. The clinical manifestations include asymptomatic in 9 patients (60.0%), defecation habits changes in 2 patients (13.3%), anal distension in 2 patients (13.3%), and abdominal distension in 2 patient (13.3%). The largest tumor diameter ≤10mm was found in 13 patients (86.7%) and >10mm in 2 patients (13.3%). All of the lesions originated from the mucous or submucosa layer. WHO grades were all NET G1. The number of tumors diagnosed by pathology in 13 patients was consistent with that observed by endoscopy, while more lesions were observed by pathology than endoscopy in two patients. Lymph node metastasis occurred in 1 patient (6.7%), and vascular or lymphatic invasion occurred in 9 patients (60.0%). Among the 13 patients with the largest tumor diameter being ≤10mm, lymphovascular invasion occurred in 8 patients (61.5%). And among the 2 patients with the largest tumor diameter of ＞10mm, lymphovascular invasion occurred in 1 patient (50.0%). 14 patients underwent endoscopic resection and 1 underwent surgical excision. Postoperative follow-up was achieved in 13 patients and no recurrence or metastasis was found. Conclusion: The true number of rectal M-NETs may be more than seen under endoscopy. Rectal M-NETs is associated with a high risk of metastasis; therefore, treatment and surveillance strategies should be more radical than single lesion.